2002
DOI: 10.1128/jcm.40.10.3689-3693.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Cytomegalovirus Glycoprotein B Recombinant Enzyme Immunoassay To Discriminate between a Recent and a Past Infection

Abstract: Fetal damage following cytomegalovirus (CMV) intrauterine infection is mostly linked to primary infection.To differentiate primary infection from nonprimary infection, immunoglobulin M (IgM) tests are not reliable enough, and measurement of the IgG avidity appears to be the method that is the most widely used at present. In the present study the performance of the Vidas (bioMérieux) avidity assay was compared with that of a new enzyme immunoassay based on the use of a recombinant CMV glycoprotein B protein (Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Many recombinant antigens have been produced and characterized for their ability to bind CMV specific antibodies (Vornhagen et al, 1994;Van Zanten et al, 1993;Sipewa et al, 2002). However, the exact composition of the antigenic mixture representative of the entire complex of CMV antigens to be used for detecting CMV antibodies is still a matter of study.…”
Section: Discussionmentioning
confidence: 98%
“…Many recombinant antigens have been produced and characterized for their ability to bind CMV specific antibodies (Vornhagen et al, 1994;Van Zanten et al, 1993;Sipewa et al, 2002). However, the exact composition of the antigenic mixture representative of the entire complex of CMV antigens to be used for detecting CMV antibodies is still a matter of study.…”
Section: Discussionmentioning
confidence: 98%
“…Two primary sera with low avidities (19% and 23%) according to conventional serology were classified as recent infection using Recomblot as these samples were IgG gB2 positive. Although gB2 is a late phase antigen, approximately 10% of sera from pregnant women with confirmed primary CMV as determined by seroconversion have antibody reactivity to gB2 [Sipewa et al, 2002]. Recent studies have also demonstrated gB2 can develop in human umbilical vein endothelial cells (HUVECs) as early as 10 days from the onset of infection [Gerna et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IgM antibodies, which appear to react specifically with HCMV may in fact be Epstein-Barr virus (EBV)-cross reactive antibodies . Demonstration of either HCMV-low avidity serum IgG (Grangeot-Keros et al, 1997) or the lack of HCMV gB (AD-1 epitope)-specific antibodies in serum specimens Sipewa et al, 2002) has been proposed as a means of differentiating between recent and past infections. Nevertheless, the diagnosis of symptomatic primary HCMV infections by serological methods often remains elusive.…”
Section: Introductionmentioning
confidence: 99%